If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -1(-8x) + 3x + -1(-11) = 0 Remove parenthesis around (-8x) 14 + -1 * -8x + 3x + -1(-11) = 0 Multiply -1 * -8 14 + 8x + 3x + -1(-11) = 0 Multiply -1 * -11 14 + 8x + 3x + 11 = 0 Reorder the terms: 14 + 11 + 8x + 3x = 0 Combine like terms: 14 + 11 = 25 25 + 8x + 3x = 0 Combine like terms: 8x + 3x = 11x 25 + 11x = 0 Solving 25 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 11x = 0 + -25 Combine like terms: 25 + -25 = 0 0 + 11x = 0 + -25 11x = 0 + -25 Combine like terms: 0 + -25 = -25 11x = -25 Divide each side by '11'. x = -2.272727273 Simplifying x = -2.272727273
| 5x-21=13+3x | | -6t-4=-3 | | -6-4=-3 | | 11x^4=x^2 | | x/2=-13/2222 | | 3x-(5/6)=4 | | x//2222=-13/2 | | 20x+3=19x+3 | | 3g-9+12g-21= | | -2(5w-7)+9=-7 | | 2x^3=40x | | y=10(-1)-3 | | n/24=30/100 | | G(p+2)=2x^2+2x+1 | | 8x-13=7x+2 | | 25=3(x+3)-x | | 2x-7y=-3 | | y=-3/2x-7 | | 5(2x-1)4x+17=5x+6(x+2) | | -(6+y-z)= | | -3-9+x=-89 | | (3x-6)/((x^2)-9) | | 5x^2-71x-282=0 | | 9x+8x-6x=41+3 | | 0.9x=0.7+0.8x | | -4y=-3x+8 | | 5x+2(5-15)=60 | | 4m+24=12m | | 112=8(6-3m)-8 | | y=10(-5)-3 | | 15+(-5)+(-2)= | | 1/3h-42/3-3=2/3h-6 |